Best Practices Pengelolaan Aset Desa Di Desa Jagalan Kabupaten Bantul - Sucahyo Heriningsih; Rusherlistyani Rusherlistyani; Dwi Sudaryati (Fakultas Ekonomi Universitas Pekalongan, 2017)
Assets are one of the village's potentials, which can supplement village income. Asset management must be professionally and optimally. Professionalism in asset management requires the participation of competent human resources, to realize accountable and transparent village financial reports by prioritizing good governance, it is expected that villages can increase community / stakeholder trust in village financial management. Village asset management should not be merely administrative, but more modern in handling village assets to improve efficiency, effectiveness and create added value in managing assets. The series of village asset management starts from planning needs and budgeting, Procurement, use, utilization, Security and maintenance, Deletion, Alienation, Administration, reporting, Assessment, Coaching, supervision, and control. This research uses descriptive method with case approach. The results of this study can be concluded: a) by applying economic principles, efficiency and effectiveness of potential assets of the village have been identified, and utilized optimally, so that the village assets have added value, b) a series of village assets management Jagalan has been implemented in accordance with Permendagri No.1 year 2016 on